The influence of agility hurdle drills, agility ring drills and speed exercises on determination - Fajar Setyo Pranyoto; Suharjana Suharjana (Nicolaus Copernicus University in Toruń, 2019)
Research objectives: (1) the difference in the effect of agility hurdle drills and ring drills on agility; (2) the difference between the effects of high and low speed on agility; and (3) the interaction between training methods and speed with agility. 2 x 2 factorial method. Futsal player research sample. 50 meter running speed test instrument, Illinois Agility Test agility. ANAVA data analysis technique α = 0.05. Results (1) There was a significant difference in the effect of agility hurdle drills and ring drills training methods on agility, p = 0.044 <0.05. The agility hurdle drills training method is better than the agility ring drills method. (2) There is a significant difference in the effect of high and low speed players on agility, p = 0.028 <0.05. Players with high speed are better than low speed. (3) There is a significant interaction between training methods and speed with agility, p = 0.004 <0.05.